2013
DOI: 10.1371/journal.pone.0062971
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PTEN Methylation Patterns in Soft Tissue Sarcomas by MassARRAY Spectrometry

Abstract: Soft tissue sarcomas (STSs) are a rare and fascinating group of diseases that can be subdivided into specific reciprocal translocations in STSs (SRTSs) and nonspecific reciprocal translocations in STSs (NRTSs). PTEN mutations are rare in STSs, suggesting that PTEN expression may be lost by alternative mechanisms such as methylation. In order to reveal whether aberrant PTEN methylation occurs in STSs, MassARRAY Spectrometry was carried to detect methylation patterns of PTEN in STSs. We evaluated methylation lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…PTEN promoter hypermethylation was also observed in approximately 39% (26 of 66 cases) of human gastric carcinomas, of which 73% (19 of 26) of the cases correlated with a loss of PTEN expression by immunohistochemistry [28]. Later studies demonstrated PTEN promoter hypermethylation in other cancers including soft tissue sarcomas, which is especially important due to the low frequency with which PTEN genomic alterations occur in this cancer subtype[30]. …”
Section: Dna Hypermethylation and Tumor Suppressor Gene Silencingmentioning
confidence: 99%
“…PTEN promoter hypermethylation was also observed in approximately 39% (26 of 66 cases) of human gastric carcinomas, of which 73% (19 of 26) of the cases correlated with a loss of PTEN expression by immunohistochemistry [28]. Later studies demonstrated PTEN promoter hypermethylation in other cancers including soft tissue sarcomas, which is especially important due to the low frequency with which PTEN genomic alterations occur in this cancer subtype[30]. …”
Section: Dna Hypermethylation and Tumor Suppressor Gene Silencingmentioning
confidence: 99%
“…Previous studies have identified that genomic alterations, including the amplification or point mutation of oncogenes and the methylation or deletion of tumor suppressor genes (e.g., MDM2 amplification, P53 mutation, and PTEN methylation), are involved in the carcinogenesis of subtype-specific STSs (Barretina et al, 2010;Hettmer et al, 2014;Ware et al, 2014;Yin et al, 2013). Moreover, p53 mutations were detected in 25.6% of STSs, the date has suggested that p53 mutations may be involved in the oncogenesis of STS (Yin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining PTEN immunohistochemical expression in 10 cases of DFSP, 4 retained the expression of PTEN and 6 showed decreased expression. 12 Therefore, it is possible that the loss of PTEN function may play a role in at least some sporadic cases of DFSP, and that our patient could potentially be more susceptible to DFSP tumorigenesis given his germline PTEN mutation.…”
Section: Discussionmentioning
confidence: 95%